Students’ Perceptions of Self and Peers Predict Self-Reports of Cheating - Henslee, Amber M.; Settles, Luke; Johnson, Sara E.; Olbricht, Gayla R. (Teaching and Learning Inquiry, 2025)
Academic dishonesty and how to address it are common concerns across higher education disciplines, but engineering students admit to higher rates of academic dishonesty than other students. However, first-year students may be particularly receptive to prevention efforts. Considering self-perception, social norming, and behavioral choice theories, we hypothesized that 1.) Students who perceived themself as ethical and more knowledgeable of the consequences for misconduct would be less likely to self-report cheating and 2.) Students who perceived cheating and plagiarism to be common would be more likely to self-report cheating. For this study, freshmen engineering students (N=703) reported their self-perception, perception of cheating and plagiarism among peers, their knowledge of the consequences for cheating, and if they had cheated. A backward elimination logistic regression model determined significant predictors of having cheated. Participants were more likely to report their cheating when they perceived cheating as common. There were significant interactions between self-ethics and perceived plagiarism, and between knowledge of consequences and perceived plagiarism interactions. Results are discussed within the context of social norming and future efforts to reduce misconduct.